Inspiring IDEA: Girls on the Run’s developmental approach to and assessment of inclusion, diversity, equity, and access programming - Weiss, Maureen R.; Kipp, Lindsay E.; Riley, Allison (Frontiers in Psychology, 2023)
Afterschool programs have the potential to enhance children’s social and emotional skills and physical activity levels. While evaluation studies of positive youth development (PYD) programs show promising impact on children’s psychosocial and behavioral outcomes, less is known about how programming is affecting youth of varying racial, ethnic, and cultural identities. Girls on the Run, a physical activity-based PYD program, has developed curricula, coach training, and programming with a lens toward inclusion, diversity, equity, and access (IDEA). The program was recognized in a rigorous review (Jones et al., 2017, 2021) as strongly committed to inclusive and equitable education. The present manuscript describes a large-scale evaluation of the degree to which Girls on the Run is successful with IDEA practices by the use of surveys, interviews, and focus groups with multiple, diverse groups—youth participants, caregivers, and coaches. Results revealed favorable responses by all participants: the program provides a safe, inclusive, and supportive climate for all youth; consists of teams with racially and ethnically diverse backgrounds; and successfully engages in strategies to reduce barriers to participation. Some areas emerged as needing further dialogue: importance of including social justice in the curriculum; recruiting more diverse coaches; and providing materials and resources in multiple languages. To sustain a culturally responsive program, Girls on the Run continues to focus evaluation efforts on social, emotional, and physical competencies, health, and well-being among diverse participants to ensure outcomes are equitable and inclusive for all youth.